Effect of the distance run and the rest periods on the static plantar pressure during a 24-hour running race - Marie Farfaro; Lucie Dumon; Charlotte Masmontet; Florian Cartayrade; Aurélien Speller; Philippe Dedieu (Asociación Española de Ciencias del Deporte, 2019)
Long-distance running has been a popular activity for decades. Beyond physical and physiological demands on runners, the lower limbs and the feet are affected in terms of their function. The aim of this study was to monitor plantar pressure over the course of a 24-h long-distance run. Twelve experienced runners participated in the study. Plantar pressure measurements were performed prior to the start of the race and regularly during the race. Rest periods and walking periods were recorded. The correlation coefficient between the ratio between the forefoot and the rearfoot and the relative distance run indicates a negative correlation; the longer the distance run, the lower the ratio between the forefoot and the rearfoot. Pressure is transferred preferentially to the rear-foot irrespective of the increase in pressure around mid-race by periods of rest and walking. Monitoring of the plantar pressure and the plantar surface area throughout the long-distance race indicated a non-linear progression of these parameters that are not in keeping with a type of deterioration. Although some of the results may contribute to the development of running injuries, our study describes a dynamical adaptation to protect against pain and the consequences of load impacts.